How Critical Thinking Skills Can Speed Up Solving Physics Problems for Senior High School - Suarjana, I Kadek (IAIN Sorong, 2023)
This research aims to investigate the relationship between critical thinking skills and the speed of junior high school students in solving physics problems. Using quantitative research methods, data was collected through critical thinking skills tests and physics problem solving exams from a number of junior high school students. The research results show that there is a significant positive correlation between students' critical thinking skills and their speed in responding to and solving physics problems. The stages of problem identification, research and data search, as well as consideration of variables and data show a strong correlation with students' speed in recognizing the essence of the problem, collecting relevant information, and analyzing physical variables more efficiently. Solution identification and solution determination skills are also positively correlated, indicating that students with high critical thinking skills can formulate and select solutions quickly. Although the results of this study provide confirmation of the importance of critical thinking skills in increasing students' speed in solving physics problems, the findings also indicate that some stages, such as relevance selection and decision analysis, could be areas of further development. Therefore, the results of this research provide a solid foundation for curriculum improvements and learning approaches that focus more on developing critical thinking skills, enabling students to be more effective and efficient in facing physics challenges at the junior high school level. The implications of this research support efforts to develop more holistic learning strategies, emphasizing the importance of integrating critical thinking skills in physics learning to achieve more optimal learning goals.